Games as a Teaching Tool in Academic Education. "The Park Manager Game" - Bernaciak, Anna; Brańka, Tomasz (Studia Oeconomica Posnaniensia, 2015)
The main objective of this study is to identify the educational effects that can be achieved through the use of innovative teaching tools in university education, in particular games. It also presents the possibility of the application of selected tools and the process of their implementation. Because of the special role of the teacher in these activities, they are described as the leaders of the activities. By undertaking particular activities, the leaders achieve the intended learning outcomes on the one hand, and help to maintain the activity of the group at the required level on the other. The empirical part of the study involves the presentation of an educational game entitled "Park Manager". The vast majority of the proposals contained in this paper, with the exception of the theoretical introduction, are based on the authors' own teaching practice, implemented at universities in Poland and abroad, and during training courses for commercial entities.